KONDISI DAN KERAGAMAN JENIS LAMUN DI PERAIRAN PANTAI PULAU AMBON - Tuapattinaya, Prelly M.J; Kurnia, Tri Santi; Latupeirissa, Louvenska Nona (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2021)
Background: The waters of Ambon Island are sea waters that are rich in flora or fauna resources, one of which is seagrass. Seagrass has significant ecological and economic value, but information about the condition and diversity of seagrass species in Ambon Island coastal waters is still relatively minimal, so this research is important to do. Methods: This research was conducted in August - November 2020 in the coastal waters of Suli Village, Poka Village, and Morela Village. The materials used in this research are seagrass and seawater which are used to measure temperature, salinity, degree of acidity (pH), and dissolved oxygen (DO). The research data were analyzed using descriptive statistics to obtain the mean value. Results: Diversity The types of seagrass that are scattered in the coastal waters of the village of Suli are Enhalus acoroides, Cymodocea serulata, Cymodocea rotundata, Halophila ovalis, Syringodium isoetifolium. Conclusion: In a study of the conditions and diversity of seagrass species in Ambon Island coastal waters, it can be concluded that there are 7 types of seagrass in Ambon Island coastal waters, with details of 7 species in the coastal waters of Suli Village, 4 species in coastal waters of Poka Village, and 5 species in coastal Village waters. Morela.